Sunitinib plus erlotinib versus placebo plus erlotinib in patients with previously treated advanced non-small-cell lung cancer: a phase III trial - Scagliotti, Giorgio V.; Thomas, Michael (Journal of clinical oncology, 2012)
Purpose: Sunitinib plus erlotinib may enhance antitumor activity compared with either agent alone in non–small-cell lung cancer (NSCLC), based on the importance of the signaling pathways involved in tumor growth, angiogenesis, and metastasis. This phase III trial investigated overall survival (OS) for sunitinib plus erlotinib versus placebo plus erlotinib in patients with refractory NSCLC. Patients and Methods: Patients previously treated with one to two chemotherapy regimens (including one platinumbased regimen) for recurrent NSCLC, and for whom erlotinib was indicated, were randomly assigned (1:1) to sunitinib 37.5 mg/d plus erlotinib 150 mg/d or to placebo plus erlotinib 150 mg/d, stratified by prior bevacizumab use, smoking history, and epidermal growth factor receptor expression. The primary end point was OS. Key secondary end points included progression-free survival (PFS), objective response rate (ORR), and safety.
Published online ahead of print on May 7, 2012
Gesehen am 20.09.2018